Формирование имиджа туристской территории города Севастополя - Журавлева, И.В. (Культура народов Причерноморья, 2013)
Статья посвящена вопросам формирования имиджа туристской территории города
Севастополя как туристско-экскурсионного района, способного обеспечить высокое качество
круглогодичных туристско-рекреационных услуг, рост благосостояния местного населения и сохранение
и воспроизводство туристского ресурсного потенциала. В статье представлен проект формирования
имиджа туристской территории города Севастополя как туристско-экскурсионного района,
способного обеспечить высокое качество круглогодичных туристско-рекреационных услуг, рост
благосостояния местного населения и сохранение и воспроизводство туристского ресурсного
потенциала. Стаття присвячена питанням формування іміджу туристської території міста
Севастополя як туристично-екскурсійного району, здатного забезпечити високу якість цілорічних
туристично-рекреаційних послуг, зростання добробуту місцевого населення і збереження і відтворення
туристського ресурсного потенціалу. У статті представлено проект формування іміджу туристської
території міста Севастополя як туристично-екскурсійного району, здатного забезпечити високу
якість цілорічних туристично-рекреаційних послуг, зростання добробуту місцевого населення і
збереження і відтворення туристського ресурсного потенціалу. The article presents the project of image formation of Sevastopol tourist territory as a tourist and
tour area, which are able to provide high quality year-round tourist and recreational services, the welfare
increase of the local population and preservation and restoration of tourist resource potential.
The project is aimed at creating the image of the tourist territory of Sevastopol in order to optimize the use of
appropriate tourist resources, generating significant revenue potential, which may be used by the city authority
to spend on improving the living conditions and promoting the welfare of its citizens.
The project includes the development of the concept of tourist area image formation for State Administration of
Sevastopol, medium and long-term marketing tourist programs for State Administration of Sevastopol with tour
operators and tour agencies, shopping malls, sports federations, committees and other structures on the given
territory. The developed project of forming tourist area image of Sevastopol implies to strengthen the main
function of the tourist-information center defining it as a coordinating and organizing start of the series of
activities.
The main effects of the project, expected in the future, are the following:
1. Economic effect: growth of tourist flows, investments increase, infrastructure development, hotel industry
development, and development of businesses that use territorial brands.
2. Social effect: increasing the level and quality of life, including an objective well-being of Sevastopol citizens.